SOCIAL AND PSYCHOLOGICAL CHARACTERISTICS OF THE INFLUENCE OF TOLERANCE IN FAMILY RELATIONS ON THE ACTIVITIES OF INTERNAL AFFAIRS OFFICERS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The concept of tolerance within family relationships plays a crucial role in shaping the psychological and social well-being of individuals, including law enforcement officers. This paper explores the impact of familial tolerance on the professional activities of law enforcement personnel, focusing on their ability to manage stress, maintain emotional stability, and enhance interpersonal communication. The study investigates how tolerant family dynamics contribute to better conflict resolution skills and overall work efficiency in Uzbekistan’s law enforcement sector. The findings highlight the significance of fostering tolerant relationships at home to improve the performance and mental health of law enforcement officers.